Dietary strategies to attenuate muscle loss during recovery from injury - Tipton, K. D. (Nutritional Coaching Strategy to Modulate Training Efficiency, 2013)
Injuries are an unavoidable aspect of participation in physical activity. Nutrition is important for optimal wound healing and recovery, but little information about nutritional support for injuries exists. Immediately following injury, wound healing begins with an inflammatory response. Excessive anti-inflammatory measures may impair recovery. Many injuries result in limb immobilization. Immobilization results in muscle loss due to increased periods of negative muscle protein balance from decreased basal muscle protein synthesis and resistance to anabolic stimuli, including protein ingestion. Oxidative capacity of muscle is also decreased. Nutrient and energy deficiencies should be avoided. Energy expenditure may be reduced during immobilization, but inflammation, wound healing and the energy cost of ambulation limit the reduction of energy expenditure. There is a theoretical rationale for leucine and omega-3 fatty acid supplementation to help reduce muscle atrophy. During rehabilitation and recovery from immobilization, increased activity, in particular resistance exercise will increase muscle protein synthesis and restore sensitivity to anabolic stimuli. Ample, but not excessive, protein and energy must be consumed to support muscle growth. During rehabilitation and recovery, nutritional needs are very much like those for any athlete desiring muscle growth. The most important consideration is to avoid malnutrition and to apply a risk/benefit approach.